Combination of adsorption and biodegradation processes for textile effluent treatment using a granular activated carbon-bioflm confgured packed column system - Soon-An, Ong; Toorisaka, Eiichi; Hirata, Makoto; Hano, Tadashi (The Research Centre for Eco-Environmental Sciences, Chinese Academy of Sciences, 2009)
Link to publisher's homepage at http://www.elsevier.com